The analgesic effect of green light on neuropathic pain: a mini-review of the literature and a proposal for future work - Dai, Wenjing; Zhang, Ying; Gu, Rui; Zhu, Xiaoyan; Leng, Yujie; Ma, Lijie; Zhang, Ming (Frontiers in Pain Research, 2025)
Medically refractory, severe, and unrelenting neuropathic pain remains a public health challenge worldwide. Green light has been found to have an analgesic effect on neuropathic pain. Interestingly, this analgesic effect is prolonged even after green light exposure. Peripheral and central mechanisms include the inhibition of the inflammatory response and the activation of the endogenous cannabinoid system and nerve circuits between the lateral geniculate nucleus and other brain regions, such as the dorsal raphe nucleus and the rostral ventromedial medulla, which may mediate the analgesic effect of green light. An increasing number of clinical studies highlight the side effects of traditional analgesics. The antinociceptive effect of green light has been proven in fibromyalgia and migraine patients. However, the effect of green light on neuropathic pain has not been reported in clinical settings. Here, we review the cellular and molecular mechanisms of the antinociceptive effect of green light. Furthermore, the green light parameters (intensity, duration, and wavelength) used in clinical trials are also summarized.